Studying Staphylococcal Leukocidins: A Challenging Endeavor - Tromp, Angelino T.; van Strijp, Jos A. G. (Frontiers in Microbiology, 2020)
Staphylococcus aureus is a well-known colonizer of the human skin and nose, but also a human pathogen that causes a wide spectrum of diseases. It is well established that S. aureus secretes an arsenal of virulence factors that have evolved to circumvent the human immune system. A major group of S. aureus virulence factors is the bi-component β-barrel pore-forming toxins, also known as leukocidins. These pore-forming toxins target specific cells of the innate and adaptive immune system by interacting with specific receptors expressed on the cell membrane. Even though still heavily debated, clinical and epidemiological studies suggest the involvement of one of the bi-component toxin, Panton-Valentine Leukocidin (PVL), as an important factor contributing to the epidemic spread and increased virulence of CA-MRSA strains. However, the host- and cell-specificity of PVL and other leukocidins, and the lack of adequate in vivo models, fuels the controversy and impairs the appropriate assessment of their role in S. aureus pathophysiology. Currently, the mechanisms of pore-formation and the contribution of PVL and other leukocidins to S. aureus pathophysiology are incompletely understood. This review summarizes our current understanding of leukocidin pore-formation, knowledge gaps, and highlights recent findings identifying novel host-factors involved in the toxin-host interface. As a result, this review furthers emphasizes the complexity behind S. aureus leukocidin cytotoxicity and the challenges associated in the quest to study and understand these major virulence factors.